Analysis of clinical and genetic features in an adolescent patient with primary ciliary dyskinesia induced by homozygous mutation in the RSPH4A gene: a case report - Xu, Wanting; Yang, Yan; Kang, Lan; Guo, Ling; Liu, Jing; Zeng, Yan; Li, Lei; Chen, Ai; Zhang, Rong; Dong, Wenbin (Frontiers in Pediatrics, 2025)
Primary ciliary dyskinesia (PCD) is a rare genetically heterogeneous disorder characterized by dysfunctional motile cilia, with or without detectable ultrastructural abnormalities. This study focuses on a homozygous mutation in the rare radial spoke head component 4A (RSPH4A) gene in a Chinese adolescent girl with PCD. The patient, an 11-year and 3-month-old girl, developed neonatal pneumonia after birth and gradually presented with persistent perennial rhinitis and recurrent productive cough. Lung CT scan indicated bronchiectasis, and whole-exome sequencing (WES) exhibited a novel pathogenic homozygous c.351dup (p. Pro118Serfs*2) frameshift mutation in the RSPH4A gene. A literature review reported that 21 pathogenic variants in RSPH4A have been discovered. WES recognized disease-causing mutations in PCD, and c.351dup (p. Pro118Serfs*2) frameshift mutation in RSPH4A may become a hotspot in Chinese patients.